2009
DOI: 10.1016/j.jad.2008.04.027
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant treatment normalizes hypoactivity in dorsolateral prefrontal cortex during emotional interference processing in major depression

Abstract: The sample was fairly homogeneous and this may limit generalizability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
137
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 234 publications
(155 citation statements)
references
References 19 publications
11
137
1
Order By: Relevance
“…15,17,27,[37][38][39][40][41][42][43][44][45][46] Our results are in agreement with those and similar findings, 6,14,47 indicating that a stronger prefrontal-parietal BOLD signal during the eliciting of emotion is a neural correlate of the effect of the drug on mood regulation. This effect appears to be independent of the clinical (therapeutic) action, because it also occurs in healthy individuals.…”
Section: Discussionsupporting
confidence: 90%
“…15,17,27,[37][38][39][40][41][42][43][44][45][46] Our results are in agreement with those and similar findings, 6,14,47 indicating that a stronger prefrontal-parietal BOLD signal during the eliciting of emotion is a neural correlate of the effect of the drug on mood regulation. This effect appears to be independent of the clinical (therapeutic) action, because it also occurs in healthy individuals.…”
Section: Discussionsupporting
confidence: 90%
“…Although the results have not always been consistent due to differences in tasks or patients' clinical profiles, fMRI studies 56,57 have also revealed a hypofunctioning dorsal cognitive control system and a hyperfunctioning emotional system. Furthermore, casecontrol studies in depressed patients without medication 58 have found elevated activation in response to negative stimuli in the amygdala, as well as either decreased or increased activation in the dorsolateral-prefrontal cortex (dlPFC) and dorsal anterior cingulate cortex, depending on task load. 59 Pilot studies of patients on antidepressants have found a reversal of this pattern as a result of mood improvement.…”
Section: Potential Neural Mechanisms Underlying the Effectiveness Of mentioning
confidence: 99%
“…59 Pilot studies of patients on antidepressants have found a reversal of this pattern as a result of mood improvement. 53,58,60 Whereas antidepressants have been hypothesized to target the amygdala and other limbic regions directly and affect a bottom-up pathway, cognitive behavioral therapy (CBT) has been proposed to operate on the dorsal cognitive control system and to affect a top-down control pathway. 52,55,61 Antidepressants appear to increase the activity of the dlPFC, 60,62 whereas CBT may decrease dlPFC activity and increase activity in the hippocampus and the dorsal cingulate.…”
Section: Potential Neural Mechanisms Underlying the Effectiveness Of mentioning
confidence: 99%
“…The attentional set-shifting test (AST) was developed to measure cognitive flexibility in rats, including extra-dimensional (ED) cognitive set-shifting, which depends critically on the functional integrity of the medial prefrontal cortex (mPFC) (Birrell and Brown, 2000). This region has been shown to be hypoactive in depressed patients and individuals exposed to chronic psychosocial stress (Stuss et al, 2000;Siegle et al, 2007;Fales et al, 2009;Liston et al, 2009). In previous studies, we found that chronic unpredictable stress (CUS) compromised the performance of rats on the ED stage of the AST (Bondi et al, 2008(Bondi et al, , 2010.…”
Section: Introductionmentioning
confidence: 99%